The fiber cone of a monomial ideal in two variables. (September 2019) - Herzog, Jürgen; Qureshi, Ayesha Asloob; Saem, Maryam Mohammadi
Abstract: By using Gröbner bases we determine in an explicit way the depth of the fiber cone and its relation ideal for classes of monomial ideals in two variables. These classes include concave and convex ideals as well as symmetric ideals.